An asymmetric PCR-based, reliable and rapid single-tube native DNA engineering strategy - Bi, Yanzhen (BioMed Central, 2012)
BACKGROUND: Widely used restriction-dependent cloning methods are labour-intensive and time-consuming, while several types of ligase-independent cloning approaches have inherent limitations. A rapid and reliable method of cloning native DNA sequences into desired plasmids are highly desired. RESULTS: This paper introduces ABI-REC, a novel strategy combining asymmetric bridge PCR with intramolecular homologous recombination in bacteria for native DNA cloning. ABI-REC was developed to precisely clone inserts into defined location in a directional manner within recipient plasmids. It featured an asymmetric 3-primer PCR performed in a single tube that could robustly amplify a chimeric insert-plasmid DNA sequence with homologous arms at both ends. Intramolecular homologous recombination occurred to the chimera when it was transformed into E.coli and produced the desired recombinant plasmids with high efficiency and fidelity. It is rapid, and does not involve any operational nucleotides. We proved the reliability of ABI-REC using a double-resistance reporter assay, and investigated the effects of homology and insert length upon its efficiency. We found that 15 bp homology was sufficient to initiate recombination, while 25 bp homology had the highest cloning efficiency. Inserts up to 4 kb in size could be cloned by this method. The utility and advantages of ABI-REC were demonstrated through a series of pig myostatin (MSTN) promoter and terminator reporter plasmids, whose transcriptional activity was assessed in mammalian cells. We finally used ABI-REC to construct a pig MSTN promoter-terminator cassette reporter and showed that it could work coordinately to express EGFP. CONCLUSIONS: ABI-REC has the following advantages: (i) rapid and highly efficient; (ii) native DNA cloning without introduction of extra bases; (iii) restriction-free; (iv) easy positioning of directional and site-specific recombination owing to formulated primer design. ABI-REC is a novel approach to DNA engineering and gene functional analysis.